Temporary Impediments to the Death Penalty in the Crime of Intentional Homicide under Imami Jurisprudence and the Iraqi Penal Code" - Abud Ajjaj Mohammad roomi, Rese.; Mohammad Reza Zafari, Asst. Prof. Dr. (lark, 2025)
The death penalty is one of the most severe punishments in criminal law, representing the maximum penalty for committing the crime of premeditated murder due to its grave violation of an individual’s right to life. However, the enforcement of this punishment is not absolute, as certain temporary impediments may arise, necessitating a postponement of execution until such obstacles are removed. This postponement is essential to uphold the principles of justice and ensure that the punishment does not conflict with legal and humanitarian values. These impediments do not imply the abolition or cancellation of the penalty but rather a delay in its implementation until the appropriate conditions are met, allowing for its enforcement without violating the fundamental rights of the convicted person. The importance of a comparative study between the provisions of Imami jurisprudence and Iraqi law lies in revealing the extent of disparity among different legal systems in defining these temporary impediments. This approach goes beyond mere legal analysis to explore the philosophical and humanitarian dimensions that govern the imposition and execution of punishments. Consequently, this subject remains a central issue in legal and human rights debates at the international level.